Levels of physical activity in people with chronic pain - Romy Parker; Emma Bergman; Anelisiwe Mntambo; Shannon Stubbs; Matthew Wills (AOSIS, 2017)
Background: People who suffer from chronic pain are thought to have lower levels of physical activity compared to healthy individuals. However, there is a lack of evidence concerning levels of physical activity in South Africans with chronic pain. Objectives: To compare levels of physical activity in a South African sample of people with chronic pain compared to matched controls. Methods: A cross-sectional study was conducted with 24 participants (12 with chronic pain and 12 in the control group matched for age, gender and residential area). Convenience sampling was used. The participants with chronic pain (12) were identified from the Groote Schuur Hospital, Chronic Pain Management Clinic (CPMC) waiting list and had not yet received any chronic pain management intervention. Healthy matched controls were selected from volunteers in the community. With the desired alpha level set at 0.05 and the power at 0.9, 45 participants were required to detect a minimum of a 50 per cent difference between groups in levels of physical activity as measured in steps per day using pedometers. The international physical activity questionnaire (IPAQ) and the brief pain inventory (BPI) were used as measures of physical activity and pain. Objective indicators of physical activity that were used included the 6-minute walk test (6MWT), repeated sit-to-stand test (RSST), 7 days of pedometry and body mass index (BMI). Results: The chronic pain group performed significantly worse on the 6MWT (335 m [30-430] vs 680 m [430-795]; U = 0.5; p < 0.01) and on the RSST (17.9 s [11.83-105] vs 7.85 s [5.5-11.5]; U = 0; p < 0.01). The chronic pain group also had significantly lower scores on pedometry (mean daily: 2985.1 [32.8-13785.4] vs 6409.4 [4207.1-15313.6]; U = 35; p < 0.03). The BMI for the chronic pain group was significantly higher than matched controls (29.36 kg/m2 [18.94-34.63] vs 22.16 kg/m2 [17.1-30.86]; U = 34; p < 0.03). Conclusion: Participants with chronic pain had a reduced capacity for physical activity. The pedometry results illustrate a range of maladaptive strategies adopted by those with chronic pain. The majority of people with chronic pain appear to avoid physical activity leading to greater disability as a result of immobility and muscle atrophy. However, a small subgroup appears to ignore their pain and push themselves physically despite their pain. This perseverance behaviour leads to further pain as a consequence of muscle and joint overuse. Both maladaptive behavioural responses result in further sensitisation of the central nervous system. The method used to target physical activity in these patients should be considered in treatment planning, specifically for physiotherapy.